Comparative Monte Carlo study of transparent protective layers for beta radiation attenuation in betavoltaic applications - Hisiroglu, Kevser A.; Akcali, Ozguir; Toker, Ozan; Icelli, Orhan (PERGAMON-ELSEVIER SCIENCE LTD, 2026)
This study investigates the beta radiation shielding and transmission performance of transparent polymers and glasses used as protective layers in commercial p-i-n diodes for betavoltaic systems. To the best of our knowledge, this study presents the first comprehensive application of the Half Absorption Thickness (HAT) metric to transparent polymers and glasses, providing a novel quantitative parameter for optimizing beta shielding performance. MCNP6.2 simulations were performed for seven beta sources (H-3, Ni-63, C-14, Pm-147, Sr-90, Y-90, Tc-99) and five materials (PMMA, SMMA, PC, Pyrex, glass) over nanometer-millimeter thicknesses. Transmission strongly depended on material type and source energy; glass attenuated 94 % of H-3 at sub-micron thickness, while PC transmitted over 30 %. The Half Absorption Thickness (HAT) metric revealed nanoscale attenuation differences, such as 600 nm in PC. Logarithmic regression models (R-2 > 0.99) allow rapid performance estimation, providing a quantitative basis for material selection in betavoltaic batteries, medical diagnostics, aerospace sensors, and radiation-hardened electronics.
Keywords: Betavoltaic battery; Beta radiation shielding; Transparent polymers; MCNP; Half absorption thickness; Chemistry; Nuclear Science & Technology; Radiology, Nuclear Medicine & Medical Imaging